2001
DOI: 10.1095/biolreprod64.3.753
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Transplantation of Equine Invasive Trophoblast1

Abstract: A system for transplanting invasive equine trophoblast (i.e., chorionic girdle) to ectopic sites has been developed as a means to study the differentiation of this tissue and to assess maternal immune responses to the conceptus tissue in a site outside the uterus. Chorionic girdle was isolated from Day 33 to 34 conceptuses and surgically placed into the vulvar mucosa or subdermal skin of recipient mares. Biopsy specimens of the graft sites for immunohistochemical staining were taken at weekly or biweekly inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 25 publications
1
35
0
Order By: Relevance
“…A recent study of ectopic transplantation of trophoblast stem cells in mice demonstrated their capacity to survive for several months and to modulate their local immune environment (Epple-Farmer et al 2009). Previous studies from our group have shown that equine chorionic girdle binucleate trophoblast cells survive for at least 28 days after transplantation in ectopic sites such as the vulvar mucosa and under the skin (Adams & Antczak 2001, de Mestre et al 2008). At 28 days post-transplantation, the trophoblast cells were terminally differentiated and restricted to the transplant site, suggesting that they do not proliferate or migrate (Adams & Antczak 2001, de Mestre et al 2008).…”
Section: Introductionmentioning
confidence: 94%
“…A recent study of ectopic transplantation of trophoblast stem cells in mice demonstrated their capacity to survive for several months and to modulate their local immune environment (Epple-Farmer et al 2009). Previous studies from our group have shown that equine chorionic girdle binucleate trophoblast cells survive for at least 28 days after transplantation in ectopic sites such as the vulvar mucosa and under the skin (Adams & Antczak 2001, de Mestre et al 2008). At 28 days post-transplantation, the trophoblast cells were terminally differentiated and restricted to the transplant site, suggesting that they do not proliferate or migrate (Adams & Antczak 2001, de Mestre et al 2008).…”
Section: Introductionmentioning
confidence: 94%
“…Those cells migrate through the uterine epithelium and form endometrial cups. The invasive trophoblast of the horse has also been investigated by means of ectopic transplantation experiments (Adams and Antczak 2001;Vagnoni et al 1995).…”
Section: Placenta Type In Mammalian Evolutionmentioning
confidence: 99%
“…Although the precise arrangement of maternal and fetal tissues is highly variable, some insight into the maternal response to the placenta is available. In the horse, invasive trophoblasts express polymorphic MHC class I molecules [4] and attract an alloresponse to paternal antigens in the endometrium or after ectopic transplantation [5]. Bovine pregnancy initiated by embryos arising from nuclear transfer (i.e., cloned embryos) is often characterized by fetal growth abnormalities, including altered placental cotyledon number [6].…”
Section: Animal Models Of Hla-g and Human Placental Mhc Class I Biologymentioning
confidence: 99%